Monitoring Voip Speech Quality for Chopped and Clipped Speech - Hines, Andrew; Skoglund, Jan; Kokaram, Anil C.; Harte, Naomi (Communications - Scientific letters of the University of Zilina, 2016)
Real-time monitoring of speech quality for VoIP calls is a significant challenge. This paper presents early work on a no-reference objective model for quantifying perceived speech quality in VoIP. The overall approach uses a modular design that will be able to help pinpoint the reason for degradations as well as quantifying their impact on speech quality. The model is being designed to work with narrowband and wideband signals. This initial work is focused on rating amplitude clipped or chopped speech, which are common problems in VoIP. A model sensitive to each of these degradations is presented and then tested with both synthetic and real examples of chopped and clipped speech. The results were compared with predicted MOS outputs from four objective speech quality models: ViSQOL, PESQ, POLQA and P.563. The model output showed consistent relationships between this model’s clip and chop detection modules and the quality predictions from the other objective speech quality models. Further work is planned to widen the range of degradation types captured by the model, such as non-stationary background noise and speaker echo. While other components (e.g. a voice activity detector) would be necessary to deploy the model for stand-alone VoIP monitoring, the results show good potential for using the model in a realtime monitoring tool.